Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/nmicrobiol.2016.182
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous division by non-ring FtsZ in the gammaproteobacterial symbiont of Robbea hypermnestra

Abstract: The reproduction mode of uncultivable microorganisms deserves investigation as it can largely diverge from conventional transverse binary fission. Here, we show that the rod-shaped gammaproteobacterium thriving on the surface of the Robbea hypermnestra nematode divides by FtsZ-based, non-synchronous invagination of its poles-that is, the host-attached and fimbriae-rich pole invaginates earlier than the distal one. We conclude that, in a naturally occurring animal symbiont, binary fission is host-oriented and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…This organism possesses an operon that encodes for a Min system, but it is not yet clear if Z-ring placement is regulated by the Min system. In another ectosymbiont of same family that also undergoes longitudinal division, it was recently shown that FtsZ accumulation occurs first at a pole proximal to the host (84) (Fig. 6C).…”
Section: Introductionmentioning
confidence: 94%
“…This organism possesses an operon that encodes for a Min system, but it is not yet clear if Z-ring placement is regulated by the Min system. In another ectosymbiont of same family that also undergoes longitudinal division, it was recently shown that FtsZ accumulation occurs first at a pole proximal to the host (84) (Fig. 6C).…”
Section: Introductionmentioning
confidence: 94%
“…Wide field and confocal microscopy of longitudinally dividing symbiotic bacteria that grow while attached with one pole on the skin of marine nematodes can initiate constriction using a discontinuous Z-elipse[72]. In these organisms constriction can also initiate from a single pole, utilizing an arc-like FtsZ structure instead of a ring [73]. Coupled with FtsZ’s strong tendency to form lateral interaction alone in vitro [74], and the large number of proteins identified as “FtsZ bundlers,” (for a review of this class of proteins see [75]) these observations supported a model in which the ring is composed of short FtsZ polymers held together in part via lateral interactions between single stranded protofilaments.…”
Section: Divisome Ultrastructure and The Role Of The “Bundlers”mentioning
confidence: 99%
“…Indeed, mutants of E. coli that constrain active FtsZ to a partial ring structure can still divide, although the cells display abnormal morphologies 11 , 12 . Recent studies have found that many bacterial species naturally initiate constriction on one side of the division site prior to becoming more symmetrical and that these asymmetric constrictions are likely promoted by relatively short FtsZ filaments that do not form a continuous ring structure 13 , 14 .…”
Section: Ftsz the Tubulin Homologmentioning
confidence: 99%